In-situ surface passivation induced by short-chain PFAS transformation products suppresses electrochemical degradation of microplastics - Shengping Yang; Yuehua Zhang; Xianfang Fan; Mengjuan Yao; Yuanji Shi; Linyan Yang; Xueming Chen (Chemical Engineering Journal, 2026)

Pollution characteristics, enrichment patterns, and progress in detoxification research of mycotoxins in maize - Jiaqi Song; Na Yang; Xueming Xu; Yamei Jin (Mycotoxin Research, 2026)

Varied mixed carbon source ratios affect nitrous oxide emissions in aerobic granular sludge systems - Yingrui Liu; Xianli Yang; Yingxin Jin; Quan Li; Shujun Zhang; Yingxin Zhao; Tingting Zhu; Xueming Chen; Bing-Jie Ni; Yiwen Liu (Bioresource Technology, 2026)

Lead and other elements in the diet of children (aged 0–7 years) across 20 Chinese provinces at a home-level survey: seasonal variations of element levels and risks in food, urine, and feces in healthy individuals - Maoyuan He; Xiaoping Li; Yu Gao; Pengyuan Jin; Zebo Yang; Jiayi Li; Xuelian Kui; Tunyang Geng; Xueming Zheng; Xu Zhang; Xiangyang Yan (Environmental Monitoring and Assessment, 2026)

Robust source tracing for solid waste via machine learning-enabled mineralogical fingerprinting - Le Lin; Changhai Ren; Shen Qu; Yang Xiao; Yin Li; Xueming Liu; Han Wang; Zhang Lin (Resources, Conservation and Recycling, 2026)

From radical/electron competition to interfacial shielding: How PFOA and its derivatives obstruct electrochemical degradation of microplastics - Yuehua Zhang; Shengping Yang; Yinghui Lin; Xianfang Fan; Mengjuan Yao; Shihua Yin; Yuanji Shi; Linyan Yang; Zhijie Chen; Bing-Jie Ni; Xueming Chen (Journal of Hazardous Materials, 2026)

Analytical solution and initial instability tendency assessment of deep elliptical tunnels in layered rock under arbitrary 3D far-field stresses - Xueming Zhang; Baoguo Liu; Zhiyun Deng; Rui Yang; Haoyang Peng (International Journal of Rock Mechanics and Mining Sciences, 2026)

Improved prediction for AFB1 in naturally contaminated peanut oil by fusing fluorescence with visible and near-infrared absorption and scattering properties - Xueming He; Yuanji Xiao; Yongnan Lu; Xiaoyun Yang; Fang Zhang (Food Control, 2026)

Delayed emission and pathway shift as drivers of N2O reduction in biological nitrogen removal with aniline exposure - Yingxin Jin; Xianli Yang; Yanying He; Xiang Li; Yingrui Liu; Tingting Zhu; Yufen Wang; Xueming Chen; Bing-Jie Ni; Yiwen Liu (Journal of Environmental Management, 2026)

Changes of aggregation and structural properties of heat-induced gluten by soybean soluble polysaccharides under acidic conditions - Tingting Hong; Yedong Feng; Na Yang; Yamei Jin; Dan Xu; Fengfeng Wu; Xianfeng Zhong; Guidong Huang; Xueming Xu (Food Structure, 2026)

Unveiling sulfur-vacancy-induced electron transfer pathways in FeNi2S4 steering peroxydisulfate activation from radical to non-radical oxidation - Yuansheng Wang; Xueming Lin; Zhicong Lan; Jiayi Li; Honghao Zeng; Hanyun Zhang; Min Yu; Jiaqu Tan; Dongya Li; Fan Yang (Chemical Engineering Journal, 2026)

Diurnal thermal dynamics and driving mechanisms in UCFZ: A XGBoost-SHAP analysis of Jinan City - Yishan Song; Xueming Li; Jun Yang; Yuqing Zhang; Xueping Cong; Zhe Li (Urban Climate, 2026)

Engineering a gradient SnO2-Sb-Nd electrode via synergistic defect and co-doping for ultrafast tetracycline degradation with robust durability - Xuening Bai; Yu Yang; Zhongxin Yang; Qiwen Zhang; Jian Zhang; Xuzhong Zeng; Miao He; Yejin Wang; Wenjing Yang; Anqi Li; Xueming Li (Journal of Environmental Chemical Engineering, 2026)

Quality optimization and shelf-life prediction of braised beef using synergistic ε-polylysine-integrated sterilization technologies - Jingrong Cheng; Zhenhua Shi; Xueming Liu; Huaigu Yang; Xuping Wang; Yaosheng Lin; Mingjun Zhu; Daobang Tang (Food Control, 2026)

Recombinant fusion subunit vaccine provides enhanced immune protection against Cryptocaryon irritans infection in grouper - Huicheng Wu; Zhengli Wei; Li Yang; Yihao Cen; Yanwei Li; Xueming Dan; Zequan Mo (Fish & Shellfish Immunology, 2026)

Assessing the NO and SO2 pollution impacts on the Δ3-carene photooxidation mechanisms - Ya Zhao; Chong Wang; Yufeng Shao; Yingqi Zhao; Yifei She; Hua Xie; Jiayue Yang; Weiqing Zhang; Gang Li; Ling Jiang; Xueming Yang (Environmental Pollution, 2026)

Characterization of T5DL·5DS-2RS, a wheat-rye chromosomal translocation with enhanced grain hardness and pre-harvest sprouting resistance - Xin Liu; Huiting Zhang; Zhenglan Cao; Yanhong Lei; Mengyu Han; LiBin Wang; Yilong Dong; Jishan Niu; Yaping Cao; Jiajia Zhao; Jun Zheng; Xueming Yang; et al. (Theoretical and Applied Genetics, 2026)

Production of eggshell-polypyrrole composites for enhanced Cr (VI) removal from wastewater: Mechanisms and optimization - Jiayin Xie; Size Li; Xinru Yang; Xueming Qin; Ping Sun; Lve Shi; Hongmin Li; Yongsheng Zhao (Journal of Water Process Engineering, 2026)

Comparison of induced magnetic field and microbial inactivation caused by different electro-technologies on fruit juice - Jin Xiao; Na Yang; Panxi Zheng; Zhichun Wu; Yamei Jin; Xueming Xu; Xiaohuang Cao (Innovative Food Science & Emerging Technologies, 2026)

Effect of high-intensity pulsed magnetic field on protein-starch interactions and quality of fresh noodles - Fan Liu; Zhuoying Wang; Na Yang; Yamei Jin; Xueming Xu (Innovative Food Science & Emerging Technologies, 2026)

Effect of superheated steam treatment on rehydration characteristics and eating quality of instant rice - Jingbo Yang; Xuepan Qi; Yajie Liu; Yamei Jin; Na Yang; Dan Xu; Xueming Xu; Fengfeng Wu (Food Research International, 2026)

Aroma profile improvement of fermented rice cake by rice aleurone layer: Comprehensive characterization and analysis based on sensomics - Yue Ma; Huang Zhang; Qiyan Zhao; Tian Yang; Jinzhong Xi; Dan Xu; Xueming Xu; Fengfeng Wu (Food Bioscience, 2026)

PRR11 as a newly identified oncogenic driver in retinoblastoma - Yu He; Xueming Ju; Huan Li; Mingze Li; Dan Zhang; Jialing Xiao; Yixiao Wu; Pu Zhang; Zhenglin Yang; Bo Gong (Science China Life Sciences, 2026)

Hydrodynamic characterization of non-breaking undular surges interacting with inclined coastal structures - Feidong Zheng; Zongliang Zhang; Qiang Liu; Xueming Wu; Yang Yang; Chao Wang; Cuixia Yao; Xiaozi Lin; Tingjie Huang (Ocean Dynamics, 2026)

Quantitative study on the impact of Stokes drift on marine oil spill transport and diffusion - Yiqiu Yang; Hongshan Duan; Juncheng Zuo; Xueming Zhu; Yuchen Liang; Xiaomei Luo; Zhen Wang (Ocean Engineering, 2026)

Spatiotemporal heterogeneity, source apportionment, and transformation-driven partitioned control of nitrate pollution in urban river network: Isotopic and Bayesian insights from the Liuxi-Baini River Basin - Weisong Chen; Lingshuo Hu; Jiguang Li; Xueming Lin; Xingjian Yang (Journal of Environmental Chemical Engineering, 2026)

Superheated steam-treated wheat flour for the preparation of low-fat short dough biscuits: Effects on dough characteristics and biscuit quality - Chang Han; Xuepan Qi; Yamei Jin; Na Yang; Dan Xu; Fengfeng Wu; Xueming Xu (Food Hydrocolloids, 2026)

Substituting straw with biochar enhances rice production and net economic benefit while reducing the carbon footprint in a double-cropping rice system - Shiqi Yang; Yanghaojun Xu; Wenyang Kuang; Wenhao Fan; Xueming Tan; Xiaohua Pan; Yanhua Zeng (Field Crops Research, 2026)

Effects of Water-Fertilizer-Tillage Management on NH₃ Volatilization and Nitrogen Deposition in a Typical South China Agricultural System - Xiaoming He; Lingling Bi; Tianyi Chen; Siqi Yang; Shujuan Zhang; Siyi Yang; Chaohui Chen; Xin Wu; Xingjian Yang; Xueming Lin; Yongtao Li; Zhen Zhang (Water, Air, & Soil Pollution, 2026)

Ferroptosis-driven cryoinjury in porcine testicular tissue: Mechanisms, antioxidant-based cryoprotection, and translational strategies for fertility preservation - Jesse Oluwaseun Ayantoye; Baigao Yang; Hang Zhang; Jianhua Dong; Xiaomeng Zhang; Haoran Song; Muhammad Shahzad; Hubdar Ali Kolachi; David Olusola Aderibigbe; Osamede Henry Osaiyuwu; Pengcheng Wan; Hongmei Pan; et al. (Animal Reproduction Science, 2026)

Role of humic substances on the removal of haloacetic acids from swimming pool water by nanofiltration - Linyan Yang; Min Tao; Jielun Jiang; Qinyu Yu; Xueming Chen; Victor W.-C. Chang (Journal of Water Process Engineering, 2026)

Photooxidation and ozonolysis of α-pinene and limonene mixtures: Mechanisms of secondary organic aerosol formation and cross-dimerization - Yingqi Zhao; Ya Zhao; Chong Wang; Yufeng Shao; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Ling Jiang; Xueming Yang (Journal of Environmental Sciences, 2026)

High-intensity pulse magnetic field treatment of cubilose gel and its response signal analysis - Fuchao Shi; Fan Liu; Yamei Jin; Jianmei Lian; Hongming Li; Na Yang; Xueming Xu; Bimal Chitrakar (Food Hydrocolloids, 2026)

Enhanced stability and bioavailability of astaxanthin via piperine co-encapsulation in whey protein fibril- sodium alginate complexes - Jingrong Cheng; Junquan Zheng; Xueming Liu; Huaigu Yang; Xuping Wang; Yaosheng Lin; Mingjun Zhu; Daobang Tang (Carbohydrate Polymers, 2026)

Spatio-temporal pattern and driving mechanism of the coupling coordination of human settlements systems - Xueming Li; Meishuo Du; Linlin Feng; Shenzhen Tian; Jun Yang (Journal of Geographical Sciences, 2026)

Analysis of critical thresholds for environmental impacts of deep-sea mining plumes in polymetallic nodule areas - Xueming Wang; Xuebao He; Juan Yang; Jianxin Xia (Acta Oceanologica Sinica, 2026)

Corrigendum to “Removal of antibiotics and estrogens by nanofiltration and reverse osmosis membranes” [J Hazard Mater 461 (2024) 132628] - Linyan Yang; Caiping Xia; Jielun Jiang; Xueming Chen; Yanbo Zhou; Cheng Yuan; Lichun Bai; Shujuan Meng; Guomin Cao (Journal of Hazardous Materials, 2026)

Comparative assessment of kinetic models for microbial inactivation in continuous-flow orange juice treated by induced electric field - Yaqian Fu; Zhang Huang; Na Yang; Yangchao Luo; Wenlong Liu; Baoqi Yin; Yamei Jin; Xueming Xu (Food Bioscience, 2026)

Rapid and non-invasive identification of the AFB1 contaminated peanut by data fusion of hyperspectral imaging and laser induced fluorescence - Yiwen Zhuang; Xiaoyun Yang; Xueming He; Peng Li; Yong Fang (Food Control, 2026)

Explaining the coexistence of complete ammonium-oxidizing bacteria and canonical nitrite-oxidizing bacteria under mainstream wastewater conditions from a substrate affinity perspective - Runan Yang; Shukang Cui; Jiaying Hou; Ying Zhu; Yuanji Shi; Meiying Xu; Linyan Yang; Xueming Chen (Environmental Research, 2026)

Simulation of dynamic piezomagnetic response during gas injection and extraction process in gas storage - Yongxin Gao; Chen Zhang; Guanqun Zhou; Chieh-Hung Chen; Xueming Zhang; Yang-Yi Sun; Cheng Yao; Zhendong Wang (Science China Earth Sciences, 2026)

Systematic overestimation of urban Parks’ cooling effects may mislead heat-governance-oriented park planning - Jun Yang; Zhe Li; Yuyu Zhou; Xue Bai; Jiaxing Xin; Xuefeng Kang; Gege Nie; Yuqing Zhang; Liang Zhou; Xiangming Xiao; Xueming Li (Landscape and Urban Planning, 2025)

Comparative studies of the NOx impacts on the photooxidation mechanisms of isomeric monoterpenes of β-pinene and limonene - Yingqi Zhao; Zhaoyan Zhang; Ya Zhao; Chong Wang; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Ling Jiang; Xueming Yang (Journal of Environmental Sciences, 2025)

Multiphysics synergistic thawing technologies for mitigating meat quality deterioration: Mechanisms, applications, and future perspectives - Huangbing Yao; Ankun Zhang; Fan Liu; Yamei Jin; Lingtao Zhang; Guoqiang Shao; Na Yang; Xueming Xu (Food Research International, 2025)

Effects of static magnetic fields on the physicochemical and flavor quality of strawberry fruit during cold storage - Fan Liu; Xiaoyue Mo; Sijian Zhou; Jian Wei; Na Yang; Yamei Jin; Xueming Xu (Food Chemistry, 2025)

Impact of rice wine jiuqu-soaking on the quality of steamed rice - Kai Wei; Kaige Chen; Shangyuan Sang; Yamei Jin; Na Yang; Dan Xu; Xueming Xu; Fengfeng Wu (Food Bioscience, 2025)

Inactivation of Geobacillus stearothermophilus spores by induced electric field in different food mediums - Liping Xue; Na Yang; Xueming Xu; Yamei Jin; Xiaohuang Cao; Huang Zhang (Food Microbiology, 2025)

Homogeneous MgF2-engineered Na surface architecture enabling uniform ion deposition in ultra-stable sodium metal batteries - Xueming Su; Junjie Fu; Lin Luo; Xiaoquan Yang; Yue Li; Weijiang Hu; Qing Li; Qingye Li; Chencheng Sun; Jun Yang; Hongwei Gu (Chemical Engineering Journal, 2025)

Effect of fish skin gelatin on gluten proteins during freeze-thaw cycles - Mengjuan Li; Shangyuan Sang; Chin Ping Tan; Lijie Zhu; Xiaojuan Tang; Xin Zhang; Zixuan Yang; Xueming Xu (Journal of Cereal Science, 2025)

Comammox-based simultaneous nitrification and denitrification in mainstream membrane-aerated biofilm reactor – A modeling study - Shukang Cui; Runan Yang; Ying Zhu; Jiaying Hou; Yuanji Shi; Meiying Xu; Linyan Yang; Xueming Chen (Environmental Research, 2025)

Effects of oat flour on rice flour and fermented rice cake: Processing properties, quality attributes, and starch digestive characteristics - Ruoyuan Xu; Zhen Dai; Xuan Wang; Jiayi Li; Yamei Jin; Na Yang; Dan Xu; Xueming Xu; Fengfeng Wu (Carbohydrate Polymers, 2025)

Inhibition effect and mechanism of actinolite dissolution characteristics on quartz flotation - Xueming Yin; Jin Yao; Bin Yang; Wanzhong Yin; Ningbo Song; Yu Xie; Jiayi Liu (Minerals Engineering, 2025)

Distinct fate of hydrazine in sulfur-driven autotrophic denitrification - Xiaxue Liao; Jingsheng Qian; Yuanji Shi; Linyan Yang; Xueming Chen (Chemical Engineering Journal, 2025)

Electro-pulsation-generated variable-valent metal triggers alternate pesticide oxidation-chlorinated byproduct reduction on ruthenium-single-atom electrode - Yangqi E; Binyao Wang; Yibo Lin; Huachang Jin; Xueming Chen; Jianmeng Chen; Jin Hur; Yang Yu; Dongzhi Chen (Journal of Hazardous Materials, 2025)

Green 2-hydroxybenzoic acid-ASDA-Na4 synergistic system induces morphology-controlled anhydrous MgCO₃ synthesis via magnesium leaching and carbonation from brucite solid waste - Jiayi Liu; Wanzhong Yin; Yulian Wang; Huili Han; Bin Yang; Xueming Yin; Jin Yao; Zhibin Zhang; Haoran Sun (Chemical Engineering Journal, 2025)

Electrochemical oxidation of aquaculture wastewater by biogas residue biochar: Effects of chloride and removal of organic pollutants - Xu Pei; Yu Meng; Chengyu Chen; Yongtao Li; Zifeng Luo; Peng Wang; Xiaoqiang Liu; Xueming Lin; Yulong Zhang; Siyi Yang; Zhen Zhang (Biomass and Bioenergy, 2025)

Anthropogenic effects on Δ3-carene photooxidation: Different oxidants induce significant changes of secondary organic aerosol formation mechanisms - Ya Zhao; Chong Wang; Yingqi Zhao; Yufeng Shao; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Ling Jiang; Xueming Yang (Atmospheric Environment, 2025)

Mechanisms and mitigation strategies of N2O emission in response to metal nanoparticles in wastewater treatment: a review - Xianli Yang; Yanying He; Yingrui Liu; Hanwei Wang; Peiyao Zhang; Tingting Zhu; Yufen Wang; Yingxin Zhao; Yindong Tong; Xueming Chen; Bing-Jie Ni; Yiwen Liu (Journal of Cleaner Production, 2025)

New insights into the remediation agent transport across the interface and contaminant removal in heterogeneous aquifer with lens - Jiayin Xie; Xueming Qin; Xinru Yang; Ruxue Liu; Xiaoyu Li; Yongsheng Zhao (Journal of Environmental Chemical Engineering, 2025)

The effect of lactic acid bacteria as a starter on the microbial community and flavors of the fermented beef-soybean paste - Jinhao Zou; Hongyun Shen; Anping Li; Xuping Wang; Huaigu Yang; Jingrong Cheng; Xueming Liu; Daobang Tang (Food Chemistry, 2025)

Competitive inhibition of hydrazine on hydroxylamine oxidation by ammonium-oxidizing bacteria and its stimulative impact on associated N2O production - Haojie Wang; Bokai Chen; Yuanji Shi; Linyan Yang; Xueming Chen (Chemical Engineering Journal, 2025)

Hydroxylamine-based cometabolism of ammonium-oxidizing bacteria: chloroquine biodegradation and associated nitrogen conversions - Bokai Chen; Haojie Wang; Yuanji Shi; Linyan Yang; Bing-Jie Ni; Xueming Chen (Journal of Environmental Management, 2025)

Effects of isoprene on the ozonolysis of Δ3-carene and β-caryophyllene: Mechanisms of secondary organic aerosol formation and cross-dimerization - Zhaoyan Zhang; Yingqi Zhao; Ya Zhao; Xiangyu Zang; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Xueming Yang; Ling Jiang (Journal of Environmental Sciences, 2025)

Mechanism investigation into static magnetic field effects on enhancing surfactin productivity by Bacillus subtilis - Yamei Jin; Sirui Chen; Qiyan Zhao; Na Yang; Yawei Ning; Xueming Xu (Food Bioscience, 2025)

Degradation of polyamide nanofiltration membranes by free chlorine and halide ions: Kinetics, mechanisms, and implications - Linyan Yang; Haixiang Yu; Huihui Zhao; Caiping Xia; Qinyu Yu; Xueming Chen; Guomin Cao; Lankun Cai; Shujuan Meng; Chuyang Y. Tang (Water Research, 2025)

Mo4+-Pb2+ redox triggers self-enhanced removal and recovery of Pb2+ with superselectivity - Yang Yu; Yangqi E; Hetao Liu; Qian Li; Huachang Jin; Xueming Chen; Jianmeng Chen; Dongzhi Chen (Water Research, 2025)

Effects of induced electric field on quality enhancement and shelf-life extension of bayberry juice during storage - Liping Xue; Zhenlei Xiao; Yangchao Luo; Yiping Chen; Huang Zhang; Na Yang; Xueming Xu; Yamei Jin (Innovative Food Science & Emerging Technologies, 2025)

Recovery of AFB1 intrinsic fluorescence in vegetable oils with continuous variations in matrices by theoretical analysis and experiments - Meng Wang; Xiaoqi Zhao; Xiaoyun Yang; Xueming He (Food Chemistry, 2025)

New insights to chlorination-induced chemical bond cleavage in polyamide membranes: Degradation mechanisms and the role of calcium and magnesium ions - Qinyu Yu; Shuang Wu; Linyan Yang; Xueming Chen; Min Tao; Yi Wu; Xiaowei He; Lichun Bai; Shujuan Meng (Chemical Engineering Journal, 2025)

Unraveling temperature effects on caproate and caprylate production from waste activated sludge - Yun Wang; Wei Wei; Donghai Yang; Lan Wu; Xueming Chen; Xiaohu Dai; Bing-Jie Ni (Bioresource Technology, 2025)

Enhanced efficacy of brucine dissolving-microneedles as a targeted delivery system in rheumatoid arthritis treatment: a comprehensive pharmacokinetic-pharmacodynamic analysis - Yunxia Wang; Changfu Yang; Wen Liu; Yongping Zhang; Qun Wang; Huanhuan Cheng; Jianan Shi; Xiaoshuang Yang; Shenglei Yang; Xueming Yao; Yonglin Wang; Xinli Song (Drug Delivery and Translational Research, 2025)

Identification, genome-wide sequencing and analysis of drug resistance genes in a novel Vibrio harveyi strain isolated from yellowfin seabream - Huang Zhihong; Liu Cuiyu; Guo Min; Peng Dikuang; Lai Chuchu; Zhu Kecheng; Dan Xueming; Yang Min; Lee Xuezhu (Aquaculture, 2025)

Revisit the role of hydroxylamine in sulfur-driven autotrophic denitrification - Xiaxue Liao; Ronghua Deng; Linyan Yang; Bing-Jie Ni; Xueming Chen (Water Research, 2025)

Identifying localized heat zones in urban heat islands from a hill and saddle perspective - Wenbo Yu; Jun Yang; Jiayi Ren; Zhenchao Zhang; Dongqi Sun; Bing Xue; Wei Sun; Xiangming Xiao; Jianhong(Cecilia) Xia; Xueming Li (Sustainable Cities and Society, 2025)

Tactfully introducing amphoteric group into electroactive membrane motivates highly efficient H2O splitting for reversible removal and recovery of nickel(II) - Yang Yu; Hetao Liu; Peng Wang; Xianwang Kong; Huachang Jin; Xueming Chen; Jianmeng Chen; Dongzhi Chen (Journal of Hazardous Materials, 2025)

Recent advances of wheat bran arabinoxylan exploitation as the functional dough additive - Muhammad Bilal; Dandan Li; Chong Xie; Runqiang Yang; Zhenxin Gu; Dong Jiang; Xueming Xu; Pei Wang (Food Chemistry, 2025)

Induced electric field as alternative pasteurization to improve microbiological safety and quality of bayberry juice - Liping Xue; Zitao Zheng; Yuhang Wu; Lingtao Zhang; Huang Zhang; Na Yang; Xueming Xu; Yamei Jin; Man Meng; Fu Wang (Food Chemistry, 2025)

Kinetics study on microbial growth and surfactin production of Bacillus subtilis ATCC 21332 under the synergistic effect of magnetic field and Mg2+ - Sirui Chen; Fuchao Shi; Fan Liu; Na Yang; Xueming Xu; Yamei Jin (Food Bioscience, 2025)

Applying layer-by-layer deposition to enhance stability and rheological behavior of emulsions: A review - Lingtao Zhang; Guoqiang Shao; Yamei Jin; Na Yang; Xueming Xu (Food Hydrocolloids, 2025)

Oxidation and nitrosation in Cantonese sausage during processing and storage-The impact of adding Prunus mume polyphenol - Jingrong Cheng; Peiyu Chen; Xueming Liu; Daobang Tang; Huaigu Yang; Mingjun Zhu (Food Control, 2025)

Comprehensive transcriptomic, proteomic, and intestinal microbiota analyses of largemouth bass (Micropterus salmoides) intestines reveal new insights into immune responses to Aeromonas hydrophila infection - Fuyan Chen; Xianhua Ouyang; Zhenping Liao; Ting Huang; Guixiang Tong; Honglian Tan; Mingxu Zhou; Xiaohua Lu; Xinxian Wei; Xueming Yang; Aiying Lei; Jianbin Li (Fish & Shellfish Immunology, 2025)

Green and sustainable bioboards: Biomanufacturing of mycelium-based composite boards with tunable properties - Guoqiang Shao; Lingtao Zhang; Dan Xu; Yamei Jin; Fengfeng Wu; Na Yang; Xueming Xu (Chemical Engineering Journal, 2025)

Sequencing the monoclonal antibody variable regions using multiple charge integration middle-down strategy and ultraviolet photodissociation - Jialiang Liu; Zheyi Liu; Heng Zhao; Chunlei Xiao; Xueming Yang; Fangjun Wang (Analytica Chimica Acta, 2025)

How Do Deep Learning Forecasting Models Perform for Surface Variables in the South China Sea Compared to Operational Oceanography Forecasting Systems? - Ziqing Zu; Jiangjiang Xia; Xueming Zhu; Marie Drevillon; Huier Mo; Xiao Lou; Qian Zhou; Yunfei Zhang; Qing Yang (Advances in Atmospheric Sciences, 2025)

Efficient degradation of chloroquine via pyrite-modified electro-Fenton yielding •OH and O2•- - Yuehua Zhang; Yinghui Lin; Yuanji Shi; Linyan Yang; Bing-Jie Ni; Xueming Chen (Journal of Cleaner Production, 2024)

Influence of low voltage programmed thawing on the quality of frozen pork and its myofibrillar protein - Xiao Zhang; Yuhang Wu; Yuchen Lin; Yamei Jin; Na Yang; Bimal Chitrakar; Jian Wei; Sijian Zhou; Xueming Xu (Innovative Food Science & Emerging Technologies, 2024)

Nature-inspired temperature-adaptive module: Achieving all-season passive thermal regulation for buildings - Lin Liang; Jianheng Chen; Kaixin Lin; Xueming Yang; Sai Liu; Chui Ting Kwok; Hao Pan; Ziai Liu; Aiqiang Pan; Siru Chen; Yihao Zhu; Wei Li; et al. (Energy and Buildings, 2024)

Unraveling the intrinsic mechanism of recyclable octahedral Fe3S4-triggered peroxydisulfate activation for contaminant degradation: The pivotal role of high-valent iron-oxo species - Jiaqu Tan; Zhuoxun Tian; Fengjie Qin; Qiaojuan Kong; Dongya Li; Fan Yang; Zhen Zhang; Yulong Zhang; Yongtao Li; Xueming Lin (Chemical Engineering Journal, 2024)

Spatio-temporal characteristics and influencing factors of Pseudo Human Settlements in Northeast China based on the Baidu Index - Xueming Li; Xiaohui Zhang; Shenzhen Tian; Mengke Gao; Jun Yang (Journal of Geographical Sciences, 2024)

Towards ecological civilization: Spatiotemporal heterogeneity and drivers of ecological quality transitions in China (2001–2020) - Jiaxing Xin; Jun Yang; Huisheng Yu; Jiayi Ren; Wenbo Yu; Nan Cong; Xiangming Xiao; Jianhong (Cecilia) Xia; Xueming Li; Zhi Qiao (Applied Geography, 2024)

Alterations in feeding preference and gastric emptying of giant freshwater prawn (Macrobrachium rosenbergii) following administration of varying quantities of fermented soybean meal - XingHui Cai; Jingyi Luo; Xiang Li; JingFeng Yang; XueMing Hua; Tao Liu (Aquaculture International, 2024)

Effect of magnetic field treatment on the softening of green chilies (Capsicum annuum L.) during storage - Liwen Wei; Jilong Wang; Xiaohan zhou; Sijie guo; Sijian Zhou; Jian Wei; Na Yang; Yangchao Luo; Xueming Xu; Yamei Jin (Food Research International, 2024)

Effects of NOx and NH3 on the secondary organic aerosol formation from α-pinene photooxidation - Yingqi Zhao; Zhaoyan Zhang; Ya Zhao; Chong Wang; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Ling Jiang; Xueming Yang (Atmospheric Environment, 2024)

How urban heat island magnifies hot day exposure: Global unevenness derived from differences in built landscape - Wenbo Yu; Jun Yang; Dongqi Sun; Jiayi Ren; Bing Xue; Wei Sun; Xiangming Xiao; Jianhong (Cecilia) Xia; Xueming Li (Science of The Total Environment, 2024)

Efficient degradation and mineralization of polyethylene terephthalate microplastics by the synergy of sulfate and hydroxyl radicals in a heterogeneous electro-Fenton-activated persulfate oxidation system - Yinghui Lin; Yuehua Zhang; Yonghao Wang; Yuancai Lv; Linyan Yang; Zhijie Chen; Bing-Jie Ni; Xueming Chen (Journal of Hazardous Materials, 2024)

Effect of constant-current pulsed electric field thawing on proteins and water-holding capacity of frozen porcine longissimus muscle - Na Yang; Huangbing Yao; Ankun Zhang; Yamei Jin; Xiao Zhang; Xueming Xu (Food Chemistry, 2024)

Effect of magnetic fields on the structure, properties, baking performance of frozen wheat dough at different frozen stage - Yamei Jin; Liwen Wei; Na Yang; Xueming Xu; Zhengyu Jin (Food Chemistry, 2024)

Improving zincophilicity and manipulating de-solvation effect enabling high-performance zinc metal anodes - Yujuan Pu; Youkui Zhang; Kaiyuan Zhan; Xuzhong Zeng; Wenjing Yang; Yunhuai Zhang; Xueming Li (Chemical Engineering Journal, 2024)

PVSPE: A pyramid vision multitask transformer network for spacecraft pose estimation - Hong Yang; Xueming Xiao; Meibao Yao; Yonggang Xiong; Hutao Cui; Yuegang Fu (Advances in Space Research, 2024)

Investigating the attribution of urban thermal environment changes under background climate and anthropogenic exploitation scenarios - Jiayi Ren; Jun Yang; Wenbo Yu; Nan Cong; Xiangming Xiao; Jianhong (Cecilia) Xia; Xueming Li (Sustainable Cities and Society, 2024)

Application of magnetic field to delay the quality changes by regulating the homeostasis of energy metabolism in green chili during storage - Liwen Wei; Na Yang; Xueming Xu; Hua Huang; Yamei Jin (Postharvest Biology and Technology, 2024)

Impact of hydrogen sulfide on anammox and nitrate/nitrite-dependent anaerobic methane oxidation coupled technologies - Xueming Chen; Siying Chen; Xinyan Chen; Yi Tang; Wen-Bo Nie; Linyan Yang; Yiwen Liu; Bing-Jie Ni (Water Research, 2024)

Suitable conditions and reduction mechanisms of Cr(VI) contaminated groundwater by in-situ bioremediation with molasses - Xinru Yang; Jiayin Xie; Xiaoyu Li; Xueming Qin; Yongsheng Zhao (Journal of Water Process Engineering, 2024)

Induced electric field pasteurization of acidic fruit juices: Engineering characteristics, simulation model, microbiological analysis - Na Yang; Zitao Zheng; Yamei Jin; Lingtao Zhang; Liping Xue; Xueming Xu; Zhenlei Xiao; Yangchao Luo (Journal of Food Engineering, 2024)

Changes in the molecular and structural of wheat gluten in the presence of zein during heating: Comparative studies on gluten, glutenin and gliadin - Tingting Hong; Tian Yang; Xinying Huo; Dan Xu; Yamei Jin; Fengfeng Wu; Junhui Zhang; Xueming Xu (Food Bioscience, 2024)

Constructing 3D sandwich-like structured Ti foam/TiO2−x/SnO2-Sb composite electrodes for the degradation of PPCPs - Anqi Li; Xuening Bai; Yuting Xie; Hebin Bao; Yu Yang; Miao He; Wenjing Yang; Qiwen Zhang; Yunhuai Zhang; Xueming Li (Chemical Engineering Journal, 2024)

Spatiotemporal evolution of surface urban heat islands: Concerns regarding summer heat wave periods - Jiayi Ren; Jun Yang; Wenbo Yu; Nan Cong; Xiangming Xiao; Jianhong Xia; Xueming Li (Journal of Geographical Sciences, 2024)

A novel method for determination of peroxide value and acid value of extra-virgin olive oil based on fluorescence internal filtering effect correction - Xiaoyun Yang; Jingyu Pei; Xueming He; Yue Wang; Liu Wang; Fei Shen; Peng Li; Yong Fang (Food Chemistry, 2024)

Electrochemical precipitation for water and wastewater treatment - Huachang Jin; Yang Yu; Xueming Chen (Process Safety and Environmental Protection, 2024)

Digestive characteristics of astaxanthin oil in water emulsion stabilized by a casein-caffeic acid–glucose ternary conjugate - Shuangwei Shen; Xueming Liu; Daobang Tang; Huaigu Yang; Jingrong Cheng (Food Chemistry, 2024)

Insight into the interaction mechanism between mulberry polyphenols and β-lactoglobulin - Qi Yuan; Lin He; Xuping Wang; Huaigu Yang; Fan Zhu; Xiaoxia Peng; Jingrong Cheng; Yaosheng Lin; Daobang Tang; Xueming Liu (Food Hydrocolloids, 2024)

Effect of induced electric field on microorganism inactivation, nutrients and physicochemical properties of milk - Na Yang; Zitao Zheng; Yamei Jin; Lingtao Zhang; Bimal Chitrakar; Xueming Xu (Food Bioscience, 2024)

Electro-oxidation of Ibuprofen using carbon-supported SnOx-CeOx flow-anodes: The key role of high-valent metal - Huachang Jin; Xiaozhi Xu; Renlan Liu; Xiaobo Wu; Xueming Chen; Dongzhi Chen; Xiangyong Zheng; Min Zhao; Yang Yu (Water Research, 2024)

Competitive enrichment of comammox Nitrospira in floccular sludge - Jiaying Hou; Ying Zhu; Jinzhong Liu; Limin Lin; Min Zheng; Linyan Yang; Wei Wei; Bing-Jie Ni; Xueming Chen (Water Research, 2024)

Effects of long-term monocropping, rotation cropping, and fertilization on energy and fuel requirements for fall moldboard plowing in a clay-loam soil - Neil B. McLaughlin; Craig F. Drury; W. Daniel Reynolds; Xueming Yang; Stephen D. Burtt (Soil and Tillage Research, 2024)

Mechanism of frozen dough deterioration and the behavior of different wheat starch types during storage - Zixuan Yang; Yamei Jin; Xueming Xu (Journal of Cereal Science, 2024)

‘Pipes & Valves’: Managing crop production and environmental impact by mitigating ammonia, nitrous oxide, and nitrate losses - Craig F. Drury; Ward Smith; Brian Grant; W. Daniel Reynolds; Xueming Yang; Lori A. Phillips (Field Crops Research, 2024)

Ce(IV)/Ce(III) redox cycle triggers hydroxyl radical production on the CeOx/carbon black flow-anode for electro-oxidation of acetaminophen - Huachang Jin; Xiaozhi Xu; Renlan Liu; Xiaobo Wu; Xueming Chen; Xiangyong Zheng; Min Zhao; Yang Yu (Chemical Engineering Journal, 2024)

Single-Cell RNA Sequencing Transcriptomics Revealed HCMV IE2-Related Microglia Responses in Alzheimer’s-Like Disease in Transgenic Mice - Fengjun Liu; Zhifei Wang; Delei Niu; Xianjuan Zhang; Fulong Nan; Shasha Jiang; Jun Li; Meng Yu; Xiaoli Yang; Shuyun Zhang; Xiaoqiong Zhou; Hui Wang; et al. (Molecular Neurobiology, 2024)
Although multiple factors are known to concur with Alzheimer’s disease (AD), the relationship between human cytomegalovirus (HCMV) and AD-like disease is unclear. Here, we propose a hypothesis that HCMV immediate-early 2 (IE2) protein promotes microglia activation and thus leads to AD-like disease. We successfully constructed IE2 transgenic mice expressing IE2 in the hippocampus. Single-cell sequencing analysis revealed that IE2 promoted the activation of microglia and upregulated the expression of disease-associated microglia genes. Differentially expressed gene analysis and pathway enrichment revealed that IE2 upregulated immune and nervous system disease-related genes. Immunohistochemical analysis showed that the expressions of both amyloid precursor protein (APP) and p-Tau were significantly upregulated in the brains of IE2 mice and were markers of AD. Taken together, these findings provide useful insights into AD-like disease activated by HCMV IE2.

Legume cover crop as a primary nitrogen source in an organic crop rotation in Ontario, Canada: impacts on corn, soybean and winter wheat yields - Xueming Yang; Craig F. Drury; W. Dan Reynolds; Mary-Anne D. Reeb (Organic Agriculture, 2024)
This study presents results from the first 5 years of an organic cropping trial in Ontario, Canada, where legume cover crops were the primary nitrogen source in a soybean-winter wheat/cover crop-corn rotation. Treatments included cover crop termination using moldboard plow (MP) or chisel plow (CP), a no-cover crop control under conventional production (CK-C), and four cover crops including summer-seeded crimson clover (CC, Trifolium incarnatum L.), summer-seeded hairy vetch (HV, Vicia villosa L. Roth), summer-seeded red clover (RC ss , Trifolium pratense L.), and frost-seeded red clover (RC fs ). Summer-seeding occurred after wheat harvest (July–August), and frost-seeding occurred in early spring (March–April). At cover crop termination, average aboveground cover crop biomass ranged from 5.9 to 8.1 Mg ha −1 , while accumulated biomass nitrogen ranged from 155 to 193 kg ha −1 . Corn grain yields were 11.6 Mg ha −1 for MP and 10.2 Mg ha −1 for CP tillage-termination method; and 13.3 Mg ha −1 for CK-C, 10.9 Mg ha −1 for RC fs , 10.6 Mg ha −1 for HV, 10.2 Mg ha −1 for CC, and 9.5 Mg ha −1 for RC ss . Organic winter wheat yields were nitrogen-limited, averaging 27% lower than CK-C. Winter wheat yields were 10–15% lower in the RC fs than in other summer-seeded cover crop treatments. Soybean yields were largely unaffected by the treatments. It was concluded that summer-seeded legume cover crops are an effective primary nitrogen source for corn, but not as effective for the winter wheat phase of the soybean-winter wheat-corn rotation.

Effects of NO2 and SO2 on the secondary organic aerosol formation from β -pinene photooxidation - Xiangyu Zang; Zhaoyan Zhang; Yingqi Zhao; Gang Li; Hua Xie; Weiqing Zhang; Guorong Wu; Xueming Yang; Ling Jiang (Journal of Environmental Sciences, 2024)

Dynamic behavior of zein-gluten interaction during extruded noodle processing - Tingting Hong; Zhiwen Tan; Tian Yang; Dan Xu; Yamei Jin; Fengfeng Wu; Xueming Xu (Food Hydrocolloids, 2024)

Anthraquinone centers modified covalent organic frameworks for boosted photocatalytic O2-to-H2O2 synthesis: Inhibiting the in-situ decomposition of H2O2 - Yu Luo; Chenchen Liu; Jiahui Liu; Xueming Liu; Yang Zhou; Xinwen Ou; Bo Weng; Jin Jiang; Bin Han (Chemical Engineering Journal, 2024)

Improving microbial production of value-added products through the intervention of magnetic fields - Sirui Chen; Yamei Jin; Na Yang; Liwen Wei; Dan Xu; Xueming Xu (Bioresource Technology, 2024)

Effects of NO and SO2 on the secondary organic aerosol formation from isoprene photooxidation - Zhaoyan Zhang; Yingqi Zhao; Ya Zhao; Xiangyu Zang; Hua Xie; Jiayue Yang; Weiqing Zhang; Guorong Wu; Gang Li; Xueming Yang; Ling Jiang (Atmospheric Environment, 2024)

Removal of antibiotics and estrogens by nanofiltration and reverse osmosis membranes - Linyan Yang; Caiping Xia; Jielun Jiang; Xueming Chen; Yanbo Zhou; Cheng Yuan; Lichun Bai; Shujuan Meng; Guomin Cao (Journal of Hazardous Materials, 2024)

Green and sustainable biomaterials: Edible bioplastic films from mushroom mycelium - Guoqiang Shao; Dan Xu; Zhuojia Xu; Yamei Jin; Fengfeng Wu; Na Yang; Xueming Xu (Food Hydrocolloids, 2024)

New insights on the preparation of amine covalent organic polymer and its adsorption properties - Yutong Hou; Aiyuan Jia; Xueming Qin; Xinru Yang; Jiayin Xie; Xiaoyu Li; Yongsheng Zhao (Environmental Pollution, 2024)

Insights into zein on rheological, structural, thermal properties of wheat dough under glutathione and azodicarbonamide, salt, or acidic conditions - Tingting Hong; Xinying Huo; Tian Yang; Yamei Jin; Dan Xu; Fengfeng Wu; Xueming Xu (Food Bioscience, 2023)

Influence of pulsed electric field on thawing of frozen pork: Physical properties, fat oxidation and protein structure - Huangbing Yao; Yamei Jin; Xiao Zhang; Na Yang; Xueming Xu (Food Bioscience, 2023)

Effect of aluminum and manganese ions on the chlorination of polyamide membranes - Linyan Yang; Jinrui Wang; Xueming Chen; Cheng Yuan; Lichun Bai; Shujuan Meng; Guomin Cao (Desalination, 2023)

Exposure of sulfur-driven autotrophic denitrification to hydroxylamine/hydrazine: Underlying mechanisms and implications for promoting partial denitrification and N2O recovery - Pengfei Huo; Ronghua Deng; Linyan Yang; Yiwen Liu; Wei Wei; Bing-Jie Ni; Xueming Chen (Chemical Engineering Journal, 2023)

Effects of mulberry pomace polysaccharide addition before fermentation on quality characteristics of yogurt - Huaxin Du; Xuping Wang; Huaigu Yang; Fan Zhu; Jingrong Cheng; Xiaoxia Peng; Yaosheng Lin; Xueming Liu (Food Control, 2023)

Model-based development of strategies enabling effective enrichment and application of comammox bacteria in floccular sludge under mainstream conditions - Ying Zhu; Jiaying Hou; Jinzhong Liu; Pengfei Huo; Linyan Yang; Min Zheng; Wei Wei; Bing-Jie Ni; Xueming Chen (Science of The Total Environment, 2023)

High thermal conductivity of porous graphite/paraffin composite phase change material with 3D porous graphite foam - Xueming Yang; Chunbo Li; YongFu Ma; He Chi; Zongjie Hu; Jianfei Xie (Chemical Engineering Journal, 2023)

Impacts of granular sludge properties on the bioreactor performing nitrate/nitrite-dependent anaerobic methane oxidation/anammox processes - Xinyan Chen; Qi Zhao; Linyan Yang; Wei Wei; Bing-Jie Ni; Xueming Chen (Bioresource Technology, 2023)

Kinetics for the reaction of Criegee intermediate CH2OO with n-butyraldehyde and its atmospheric implications - Siyue Liu; Yang Chen; Haotian Jiang; Jiayu Shi; Hongbin Ding; Xueming Yang; Wenrui Dong (Atmospheric Environment, 2023)

Preparation and characterization of PMT-TiO2-NTs@NiO–C/Sn–Sb composite electrodes by a two-step pulsed electrodeposition method for the degradation of crystalline violet - Anqi Li; Xuening Bai; Yuting Xie; Pengyang Xia; Hebin Bao; Miao He; Xuzhong Zeng; Wenjing Yang; Xueming Li (Chemosphere, 2023)

Stable and recyclable FeS-CMC-based peroxydisulfate activation for effective bisphenol A reduction: performance and mechanism - Zijun Tan; Jiaqu Tan; Zijiang Yang; Wenxin Sun; Aiying Guo; Jinjin Wang; Yongtao Li; Xueming Lin (Chemosphere, 2023)

Subtle introduction of membrane polarization-catalyzed H2O dissociation actuates highly efficient electrocoagulation for hardness ion removal - Yang Yu; Mengyu Zhang; Qian Li; Xueming Chen; Dongzhi Chen; Huachang Jin (Water Research, 2023)

The effects of mulberry polyphenols on the digestibility and absorption properties of pork myofibrillar protein in vitro - Jingrong Cheng; Daobang Tang; Huaigu Yang; Xuping Wang; Yaosheng Lin; Xueming Liu (Meat Science, 2023)

N-doped biochar mediated peroxydisulfate activation for selective degradation of bisphenol A: The key role of potential difference-driven electron transfer mechanism - Jiaqu Tan; Xinmin Chen; Mengru Shang; Jiannan Cui; Dongya Li; Fan Yang; Zhen Zhang; Haotian Zhang; Qitang Wu; Yongtao Li; Xueming Lin (Chemical Engineering Journal, 2023)

Effect of weak magnetic field on the water-holding properties, texture, and volatile compounds of pork and beef during frozen storage - Fan Liu; Na Yang; Lingtao Zhang; Yamei Jin; Zhengyu Jin; Xueming Xu (Food Bioscience, 2023)

An oral nano-antioxidant for targeted treatment of inflammatory bowel disease by regulating macrophage polarization and inhibiting ferroptosis of intestinal cells - Jing Yang; Yunhao Bai; Shuilin Shen; Xinyue Tao; Chengyu Ma; Bowen Fu; Qihao Dai; Jian Wu; Zhengjie Meng; Qingmin Sun; Xueming Li; Hao Ren (Chemical Engineering Journal, 2023)

Failure experiment on CFRP-strengthened prestressed concrete cylinder pipe with broken wires - Kejie Zhai; Hongyuan Fang; Bin Li; Chengchao Guo; Kangjian Yang; Xueming Du; Mingrui Du; Niannian Wang (Tunnelling and Underground Space Technology, 2023)

Magnetic field delays the senescence of strawberries by maintaining energy state and regulating respiratory metabolism - Fan Liu; Na Yang; Lingtao Zhang; Bo Cui; Yamei Jin; Zhengyu Jin; Xueming Xu (Postharvest Biology and Technology, 2023)

Putative inactivation mechanism and germicidal efficacy of induced electric field against Staphylococcus aureus - Lingtao Zhang; Na Yang; Yamei Jin; Xueming Xu (Food Microbiology, 2023)

Reductive sequestration of Cr(VI) in soil and groundwater using Ca-Fe-S microparticles - Jianle Wang; Xueming Liu; Hong Deng; Dongye Zhao; Qiulin Yang; Zhihua Zhu (Journal of Environmental Chemical Engineering, 2023)

Genome-wide analysis of genetic pleiotropy and causal genes across three age-related ocular disorders - Xueming Yao; Hongxi Yang; Han Han; Xuejing Kou; Yuhan Jiang; Menghan Luo; Yao Zhou; Jianhua Wang; Xutong Fan; Xiaohong Wang; Mulin Jun Li; Hua Yan (Human Genetics, 2023)

Self-destructive microchip: Support-free energetic film of BiOBr/Al/Bi2O3 nanothermites and its destructive performance - Haifeng Yang; Zhiqiang Qiao; Weimiao Wang; Pengfei Tang; Shuaishuai Man; Xiaodong Li; YuTing Xie; Deyun Tang; Xueming Li; Guangcheng Yang (Chemical Engineering Journal, 2023)

Towards efficient heterotrophic recovery of N2O via Fe(II)EDTA-NO: A modeling study - Ronghua Deng; Pengfei Huo; Xueming Chen; Zhijie Chen; Linyan Yang; Yiwen Liu; Wei Wei; Bing-Jie Ni (Science of The Total Environment, 2023)

Regulation on the quality of yogurt by phenolic fraction of mulberry pomace supplemented before and after fermentation - Huaxin Du; Xuping Wang; Huaigu Yang; Fan Zhu; Jie Liu; Jingrong Cheng; Yaosheng Lin; Daobang Tang; Xueming Liu (Food Control, 2023)

Model-based evaluation of N2O recovery as an energy source in sulfur-driven NO-based autotrophic denitrification - Pengfei Huo; Ronghua Deng; Xueming Chen; Linyan Yang; Yiwen Liu; Lan Wu; Wei Wei; Bing-Jie Ni (Chemical Engineering Journal, 2023)

Spatiotemporal evolution of pseudo human settlements: case study of 36 cities in the three provinces of Northeast China from 2011 to 2018 - Shenzhen Tian; Xueming Li; Jun Yang; Hui Wang; Jianke Guo (Environment, Development and Sustainability, 2023)

The effect of nitrification inhibitors on the aerobic biodegradation of tetracycline antibiotics in swine wastewater - Linyan Yang; Cheng Yuan; Xueming Chen; Weibo Xue; Guomin Cao; Shujuan Meng; Lichun Bai (Chemosphere, 2023)

Instrumental role of bioreactors in nitrate/nitrite-dependent anaerobic methane oxidation-based biotechnologies for wastewater treatment: A review - Xinyan Chen; Xueming Chen; Raymond Jianxiong Zeng; Wen-Bo Nie; Linyan Yang; Wei Wei; Bing-Jie Ni (Science of The Total Environment, 2023)

Improved physicochemical stability and bioaccessibility of astaxanthin-loaded oil-in-water emulsions by a casein-caffeic acid–glucose ternary conjugate - Jingrong Cheng; Shuangwei Shen; Huaigu Yang; Daobang Tang; Xuping Wang; Yaosheng Lin; Xueming Liu (Food Research International, 2023)

Membrane deposition electrodialysis for cooling water treatment: Ion step removal and stable membrane regeneration - Yang Yu; Dongzhi Chen; Haoyang Liu; Xuejiao Zhang; Xueming Chen; Huachang Jin (Chemical Engineering Journal, 2023)

Underwater self-sustaining combustion and micro-propulsion properties of Al@FAS-17/PTFE-based direct-writing nanothermite - Haifeng Yang; Chuanhao Xu; Weimiao Wang; Pengfei Tang; Xiaodong Li; Shanshan He; Hebin Bao; Shuaishuai Man; Deyun Tang; Xueming Li; Guangcheng Yang; Zhiqiang Qiao (Chemical Engineering Journal, 2023)

Efficient activation of peroxydisulfate by a novel magnetic nanocomposite lignin hydrogel for contaminant degradation: Radical and nonradical pathways - Jiaqu Tan; Jinjin Wang; Zijun Tan; Min Yu; Zijiang Yang; Zongling Ren; Yongtao Li; Yulong Zhang; Xueming Lin (Chemical Engineering Journal, 2023)

De novo genome assembly and annotation of Holothuria scabra (Jaeger, 1833) from nanopore sequencing reads - Honglin Luo; Guanghua Huang; Jianbin Li; Qiong Yang; Jiajie Zhu; Bin Zhang; Pengfei Feng; Yongde Zhang; Xueming Yang (Genes & Genomics, 2022)

Spatial differentiation of comprehensive suitability of urban human settlements based on GIS: a case study of Liaoning Province, China - Yingying Guan; Xueming Li; Jun Yang; Songbo Li; Shenzhen Tian (Environment, Development and Sustainability, 2022)

Study on the heat transfer in different aquifer media with different groundwater velocities during thermal conductive heating - He Sun; Xueming Qin; Xinru Yang; Yongsheng Zhao (Environmental Science and Pollution Research, 2020)

The 2012 Flash Drought Threatened US Midwest Agroecosystems - Cui Jin; Xue Luo; Xiangming Xiao; Jinwei Dong; Xueming Li; Jun Yang; Deyu Zhao (Chinese Geographical Science, 2019)

Spinal Cord Stimulation for Pain Treatment After Spinal Cord Injury - Qian Huang; Wanru Duan; Eellan Sivanesan; Shuguang Liu; Fei Yang; Zhiyong Chen; Neil C. Ford; Xueming Chen; Yun Guan (Neuroscience Bulletin, 2019)

Preparation and Evaluation of Mosapride Citrate Dual-Release Dry Suspension - Kuntang Liu; Zhengjie Meng; Yang Li; Jiwei Liu; Yan Xu; Yonglu Wang; Xueming Li (AAPS PharmSciTech, 2019)

Spatial differentiation of China’s summer tourist destinations based on climatic suitability using the Universal Thermal Climate Index - Jun Yang; Zhenchao Zhang; Xueming Li; Jianchao Xi; Zhangxian Feng (Theoretical and Applied Climatology, 2018)

Impact of Accessibility on Housing Prices in Dalian City of China Based on a Geographically Weighted Regression Model - Jun Yang; Yajun Bao; Yuqing Zhang; Xueming Li; Quansheng Ge (Chinese Geographical Science, 2018)

Specific N-glycan alterations are coupled in EMT induced by different density cultivation of MCF 10A epithelial cells - Qingsong Xu; Xueming Niu; Wenjing Wang; Wen Yang; Yuguang Du; Jianguo Gu; Linsheng Song (Glycoconjugate Journal, 2017)

Characterization of transformed soybean strains expressing GbNPR1 and HrpZpsg12 genes for disease resistance - Yang Song; Xueming Zhang; Piwu Wang; Zhenku Liu; Huanyu Dong; Jian Ma; Yongping Fu; Zhuo Zhang (Euphytica, 2016)

An engineered non-oxidative glycolysis pathway for acetone production in Escherichia coli - Xiaoyan Yang; Qianqian Yuan; Yangyang Zheng; Hongwu Ma; Tao Chen; Xueming Zhao (Biotechnology Letters, 2016)

Spatio-temporal differentiation of residential land for coastal town: A case study of Dalian Jinshitan - Jun Yang; Jing Sun; Hongdan Zhao; Jianchao Xi; Xueming Li (Chinese Geographical Science, 2016)

Urban green space, uneven development and accessibility: a case of Dalian's Xigang District - Jun Yang; Chuang Li; Yuechen Li; Jianhao Xi; Quansheng Ge; Xueming Li (Chinese Geographical Science, 2015)

Improved succinate production in Corynebacterium glutamicum by engineering glyoxylate pathway and succinate export system - Nianqing Zhu; Huihua Xia; Jiangang Yang; Xueming Zhao; Tao Chen (Biotechnology Letters, 2014)

Effects of tillage management on infiltration and preferential flow in a black soil, Northeast China - Ruqin Fan; Xiaoping Zhang; Xueming Yang; Aizhen Liang; Shuxia Jia; Xuewen Chen (Chinese Geographical Science, 2013)

Germinated Brown Rice and Its Role in Human Health - Fengfeng Wu; Na Yang; Alhassane Touré; Zhengyu Jin; Xueming Xu (Critical Reviews in Food Science and Nutrition, 2013)

Responses of CO2 efflux from an alpine meadow soil on the Qinghai Tibetan Plateau to multi-form and low-level N addition - Huajun Fang; Shulan Cheng; Guirui Yu; Jiaojiao Zheng; Peilei Zhang; Minjie Xu; Yingnian Li; Xueming Yang (Plant and Soil, 2012)

Association of B3GNT5 Polymorphisms with Susceptibility to ETEC F4ab/ac in the White Duroc × Erhualian Intercross and 15 Outbred Pig Breeds - Jing Ouyang; Weihong Zeng; Jun Ren; Xueming Yan; Zhiyan Zhang; Ming Yang; Pengfei Han; Xiang Huang; Huashui Ai; Lusheng Huang (Biochemical Genetics, 2012)

Influence of current and previous crops on soil basal and potential denitrification rates - Xiaobin Guo; Craig F. Drury; Xueming Yang; W. Daniel Reynolds; Renduo Zhang (Biology and Fertility of Soils, 2011)

Efficient Encapsulation of Chloroform with Cryptophane-M and the Formation of Exciplex Studied by Fluorescence Spectroscopy - Yanqi Shi; Xueming Li; Jianchun Yang; Fang Gao; Chuanyi Tao (Journal of Fluorescence, 2011)

A porphyritic copper (gold) ore-forming model for the Shaxi-Changpushan district, Lower Yangtze metallogenic belt, China: geological and geochemical constraints - Xiaoyong Yang; Xueming Yang; Zhengwei Zhang; Yueyu Chi; Liangfan Yu; Qianming Zhang (International Geology Review, 2011)

Different genes can be responsible for crown rot resistance at different developmental stages of wheat and barley - Xueming Yang; Jun Ma; Haobing Li; Hongxiang Ma; Jinbao Yao; Chunji Liu (European Journal of Plant Pathology, 2010)

Exposure to lanthanum compound diminishes LPS-induced inflammation-associated gene expression: involvements of PKC and NF-κB signaling pathways - Fei Guo; Yuanlei Lou; Nianhua Feng; Guohui Li; An Xie; Xueming Huang; Yang Wang (BioMetals, 2010)

Erratum to: A genome-wide scan for quantitative trait loci affecting serum glucose and lipids in a White Duroc × Erhualian intercross F2 population - Rongrong Chen; Jun Ren; Wanbo Li; Xiang Huang; Xueming Yan; Bin Yang; Yinggong Zhao; Yuanmei Guo; Huirong Mao; Lusheng Huang (Mammalian Genome, 2010)

A genome-wide scan for quantitative trait loci affecting serum glucose and lipids in a White Duroc × Erhualian intercross F2 population - Rongrong Chen; Jun Ren; Wanbo Li; Xiang Huang; Xueming Yan; Bin Yang; Yinggong Zhao; Yuanmei Guo; Huirong Mao; Lusheng Huang (Mammalian Genome, 2009)

Quantitative trait loci for porcine baseline erythroid traits at three growth ages in a White Duroc × Erhualian F2 resource population - Zhengzhi Zou; Jun Ren; Xueming Yan; Xiang Huang; Shujin Yang; Zhiyan Zhang; Bin Yang; Wanbo Li; Lusheng Huang (Mammalian Genome, 2008)

The Porcine Nuclear Receptor Co-repressor 1 (NCOR1) Gene: Chromosome Location, Expression Profile, and Polymorphism - Kaixuan Yang; Jun Ren; Junwu Ma; Xueming Yan; Lusheng Huang (Biochemical Genetics, 2007)

New evidence from a calcite-dolomite carbonatite dyke for the magmatic origin of the massive Bayan Obo ore-bearing dolomite marble, Inner Mongolia, China - M. J. Le Bas; Yang Xueming; Rex N. Taylor; B. Spiro; J. A. Milton; Zhang Peishan (Mineralogy and Petrology, 2007)

Copper content and its distribution in soils of Tibet - Zhang Xiaoping; Yan Xiuyi; Yang Xueming (Journal of Geographical Sciences, 2002)